The transmission of affect - Brennan, Teresa, 1952-2003 (Cornell University Press, 2004)
The idea that one can soak up someone else's depression or anxiety or sense the tension in a room is familiar. Indeed, phrases that capture this notion abound in the popular vernacular: negative energy, dumping, you could cut the tension with a knife. This book deals with the belief that the emotions and energies of one person or group can be absorbed by or can enter directly into another. The ability to borrow or share states of mind, once historically and culturally assumed, is now pathologized, as Teresa Brennan shows in relation to affective transfer in psychiatric clinics and the prevalence of psychogenic illness in contemporary life. To neglect the mechanism by which affect is transmitted has serious consequences for science and medical research. Brennan's theory of affect is based on constant communication between individuals and their physical and social environments. This book details the relationships among affect, energy, and new maladies of the soul, including attention deficit disorder, chronic fatigue syndrome, codependency, and fibromyalgia.